One-device colonoscopy: feasibility, cost savings, and plastic waste reduction by procedure indication, when performed by a high detecting colonoscopist - Rex, Douglas K.; Gallagher, Jackson A.; Lahr, Rachel E.; Vemulapalli, Krishna C.; Sharma, Prateek; Hassan, Cesare (Endoscopy, 2023)
Background Cold forceps and snares are each effective for removing polyps of 1–3 mm, while snares are more effective for polyps of 4–10 mm in size. If, in the same patient, polyps of 1–3 mm are removed with forceps and those of 4–10 mm with snares, two devices are used. If cold snares are used to resect all lesions of 1–10 mm (one-device colonoscopy), there is a potential for lower costs and less plastic waste.Methods A single high detecting colonoscopist prospectively measured the feasibility of cold snaring all colorectal lesions of ≤10 mm in size, along with the associated costs and plastic waste reduction.Results 677 consecutive lower gastrointestinal endoscopies (not for inflammatory bowel disease) were assessed. Of 1430 lesions of 1–3 mm and 1685 lesions of 4–10 mm in size, 1428 (99.9%, 95%CI 99.5%–100%) and 1674 (99.3%, 95%CI 98.8%–99.7%), respectively, were successfully resected using cold snaring. Among 379 screening and surveillance patients, universal cold snaring of lesions ≤10 mm saved 35 and 47 cold forceps per 100 screening and surveillance patients, respectively.Conclusion Cold snare resection of all lesions ≤10 mm (one-device colonoscopy) was feasible, and reduced costs and plastic waste.